HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN MELAKUKAN LATIHAN FISIK DAN TERAPI INSULIN PADA PASIEN DIABETES MELITUS TIPE 1 DI POLIKLINIK PENYAKIT DALAM RSUD DR. ABDOER RAHEM SITUBONDO - Annisaa Zahra Firdausi; Sriyono Sriyono; Candra Panji Asmoro (Universitas Airlangga, 2019)
Introduction: Diabetes mellitus (DM) is one of the chronic disease characterized by elevation of blood glucose concentration. Non-adherence to diabetes treatment increases the risk of disease complication. Family support is an important thing to determine adherence scale in diabetes treatmenteffort. The aim of this study was to identify correlating of family support with physical activity and insulin therapy adherence in patient with type 1 DM.Methods: A cross sectional design was used in this study. The population of this study was all of patient with type 1 diabetes mellitus that ever examination to the internal diseases polyclinic. Total sample was 58 respondents, taken withpurposive sampling technique. The independent variable was family support, and the dependent variables were physical activity adherence and insulin therapy adherence. Data were collecting used questionnaire and analyzed using Spearman’s Rho with α≤0.05.Result: Result showed that 32,76% patient with type 1 DM had good family support, 63,8% had good enough family support, and 3,44% had less family support. Researcher found that 56,9% patient had physical activity adherence and 81,1% patient had insulin therapy adherence (34,5% for good adherence and 46,6% for good enough adherence). Therapy adherence in patient with type 1 DM had significant correlation with family support (ρ=0.000, r=0.553 for physical activity and ρ=0.000, r=0.509 for insulin therapy).Conclusion: It can be concluded that family support has correlation with physical activity and insulin therapy adherence. Further studies need to identify the correlation of that variables to each family support dimension to determine the most influence of family support dimension.